2016
DOI: 10.1093/rheumatology/kew207
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholines to phosphatidylcholines ratio predicts advanced knee osteoarthritis

Abstract: We identified the ratio of lysoPCs to PCs as a novel metabolic marker for predicting advanced knee OA. Further studies are required to examine whether this ratio can predict early OA change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 50 publications
4
72
0
Order By: Relevance
“…These results are in agreement with previous reports in which 16 O exhibited a higher degree of change in lipids compared to 1 H [28,29]. An increase in overall plasma PC levels with a concomitant rise in LysoPCs levels is suggestive of oxidative stress and inflammation upon exposure to 16 O [30]. Alterations in metabolome following exposure to low dose high-LET radiation have previously been reported by our group [31].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previous reports in which 16 O exhibited a higher degree of change in lipids compared to 1 H [28,29]. An increase in overall plasma PC levels with a concomitant rise in LysoPCs levels is suggestive of oxidative stress and inflammation upon exposure to 16 O [30]. Alterations in metabolome following exposure to low dose high-LET radiation have previously been reported by our group [31].…”
Section: Discussionsupporting
confidence: 93%
“…Plasmatic lysophosphatidylcholine to phosphatidylcholine ratio was identified as a potential new OA biomarker for predicting advanced knee OA. Besides, it was confirmed that BCAAs to histidine ratio was associated with knee OA ( 47 ).…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, none of the measured lipids correlated with OA severity within the hCRP-tg group. Lysophosphatidylcholines (LPC) to phosphatidylcholines (PC) ratio, as a general indicator of inflammatory status and possible predictor of advanced knee OA in humans 24 , dropped shortly after HFD switch (hCRP-tg: from 0.83 [0.62e1.10] to 0.70 [0.38e0.80]; wild- Fig. 2(A).…”
Section: Lipid Metabolism Comparable Between Genotypesmentioning
confidence: 99%